Effect of pH on Swelling Ratio and Fluorescence of Quantum Dots (QDs) Based Hydrogel (CuInS2/ZnS QDs) - Permadi, Adi; Hadi, Sofyan; Sinaga, Alexander MT; Pitoyo, Joko; Chang, Jia-Yaw (Universitas Ahmad Dahlan, 2023)
Quantum dots (QDs) are semiconductor materials possessing a distinct electrical order and physical dimensions less than the excitation of the Bohr radius. The innovative combination of hydrogel and QDs has a broad range of applications in critical areas like the environment, health, and energy. QDs hydrogel has been applied as a biosensor and in the waste processing industry. The main characteristics of QDs hydrogel are fluorescence and swelling ratio. In the waste processing industry, the swollen hydrogel provides a more porous matrix that allows heavy metal to penetrate the hydrogels via passive diffusion. In the biosensor application, QDs hydrogel can be used as active sensors by changing the fluorescence properties when reacting with analytes, or by conjugating antibodies to the dot surface to act as passive label probes. This study aims to study the effect of pH on the fluorescence and swelling ratio of CuInS2/ZnS hydrogel. CuINS2/ZnS hydrogel is synthesized by sonication a mixture consisting of QDs (CuInS2/ZnS), N-(3-aminopropyl) methacrylate, polyethylene glycol methacrylate, methylene bis acrylamide, and ammonium persulfate solution for 5 min with amplitude of 20 kHz. CuInS2/ZnS acts as QDs component, while N-(3-aminopropyl) methacrylate, polyethylene glycol methacrylate, methylene bis acrylamide, and ammonium persulfate act as hydrogel synthesizing components. The QDs hydrogel was then immersed in water with varying pH to observe the effect of pH on fluorescence and swelling ratio. The results show that increasing pH will reduce the swelling ratio and increase the fluorescence strength. CuInS2/ZnS hydrogel has a maximum swelling ratio at a pH of 5 and provides strong fluorescence at pH of 7, 9, and 11. The result also revealed that CuInS2/ZnS hydrogel has sufficient fluorescence and swelling ratio characteristic at the pH level of the biological fluid of the human body namely 7.35-7.45, this suggests the biological application of CuInS2/ZnS hydrogel such as for drug delivery and biosensing.